Preparation and Characterization of Ceramics from Coal Fly Ash - Bhagat, Neha; S. Batra, Vidya; Katyal, Deeksha (Asian Journal of Chemistry, 2010)
Fly ash is produced in large quantities from thermal power plants utilizing coal as fuel. While many applications of fly ash such as cement, construction, bricks etc. are being explored, a large share of fly ash is still unutilized. One of the applications being examined for fly ash utilization is the production of glass and glass ceramics. This study reports the investigation on sintering/ melting of fly ash with additives with the objective of obtaining ceramics using coal fly ash from a thermal power plant near Delhi. Attempts were made to melt mixtures of fly ash with different additives by subjecting them to temperatures of 850, 900 and 950 ºC. The samples showed different extent of sintering or melting based on the additives. X-ray diffraction analysis of the samples showed them to be polycrystalline in nature with crystalline phases dependent on the initial composition of the sample.